Pengaruh Pendekatan Andragogi terhadap Keterampilan Pemecahan Masalah Peserta Didik Sekolah Menengah Atas dalam Pembelajaran Biologi - Farza Safirda; Hafnati Rahmatan; Wiwit Artika; Ismul Huda; Safrida Safrida (Jurnal Penelitian Pendidikan IPA, 2024)
The andragogy approach is learning that directs students to independently solve problems. Students' low solving skills can be seen from the lack of student activity in the learning process resulting in low learning outcomes. The aim of the research is to determine the effect of the andragogy approach on students' problem solving skills in biology learning. The method used is quasi experimental. The research design is a pretest-posttest nonequivalent control group design. The research population was biology teachers in class XI and class XI high school students, totaling 239 people. The sample used a purposive sampling technique with a total of 144 students. Data on problem solving skills using case study questions and teacher interviews. Data analysis used the normalized gain test and independent sample t-test. The results of data analysis show that there is a significant difference between the average N-gain with a result of P = 0.001. The teacher's perspective shows that the andragogy approach improves students' problem solving skills. The research conclusion is that there is an influence of the andragogy approach on students' problem solving skills in biology learning.